La ciencia, la tecnología y los átomos en el contexto de las relaciones India-China: fetiche y tabú - González Castañeda, Mario (El Colegio de México, 2010)
Science and technology acquired importance in India and China in the twentieth century as promoters of progress and national development, and as mechanisms for generating secular knowledge. This explains why nuclear energy came to represent the most evident expression of Western science and modernity in those societies. This article examines the processes through which this particular understanding of science and technology in India and China led to uncritical adoption and replication of imperial knowledge by local elites in the first half of the twentieth century. The foundation of scientific and educational institutions modelled on those of Europe generated geopolitical spaces for European knowledge. This in turn led to the creation of an international hierarchy of knowledge, in which pre-colonial non-European epistemological productions came to be viewed as inferior. By the time India gained independence and China emerged from the European colonial experience, local elites in both countries, anxious to catch up with ‘Western modernity’, turned to scientific and educational institutions with greater zeal to speed up ‘progress’ and national development.